Turn Taking Strategy in the 2020's American Presidential Debate - Sa'adah, Zulfa Nur Baiti (Journal of Literature, Linguistics, & Cultural Studies, 2022)
The aim of the study was to identify the kinds of turn taking strategies used in the first American Presidential Debate in 2020 between Donald Trump and Joe Biden, as well as to classify the functions of the turn taking that occured in the first American Presidential Debate in 2020 between Donald Trump and Joe Biden. The researcher employed a descriptive qualitative approach because the data were derived from Donald Trump's and Joe Biden's utterances on YouTube video, which was transcribed and analyzed using Sterntörm's (2014) theory of turn taking strategy; taking the turn strategy, holding the turn strategy, and yielding the turn strategy. The data were analyzed by determining the context, categorizing the data based on the theory, analyzing and interpreting the data, and drawing conclusion based on the findings. The findings revealed 35 data from Donald Trump’s utterances, with the most strategy used was alert that occurred twelve times, while he never used hesitant start strategy. On the other hand, 20 data were obtained from Joe Biden’s utterances. In fact, Joe Biden also employed alert strategy as the most utilized strategy which was the same as Donald Trump, but the occurrence was only five times. In addition, Joe Biden did not apply four turn taking strategies which were hesitant start, metacomment, silent pause, and appealing. One important point to note was that both candidates utilized alert as the most used strategy, which functioned as interrupting the other speaker by raising the tone of his voice in order to attract the attention of the interlocutor.